Communicating your vision - Cartwright, Talula (Ideas into action guidebooks., 2006)
"In this guidebook we suggest many ways to communicate a vision. We also discuss how to deal with a resistant audience and what to do in the event that you yourself are resistant. You'll learn how to communicate a vision to others in ways that will help them understand it, remember it, and then go on to share it themselves"--Resource description page